Country risk impacts on export costs of green hydrogen and its synthetic downstream products from the Middle East and North Africa - Julia Terrapon-Pfaff; Josua Braun; Sibel Raquel Ersoy; Magdolna Prantner; Jürgen Kern; Peter Viebahn (Frontiers in Energy Research)
Green hydrogen, produced from renewable energy sources such as wind and solar, is increasingly recognized as a critical enabler of the global energy transition and the decarbonization of industrial and transport sectors. The successful adoption of green hydrogen and its derivatives is closely linked to production costs, which can vary substantially between countries, depending not only on resource potential but also on country-specific financing conditions. These differences arise from country-specific risk factors that affect the costs of capital, ultimately influencing investment decisions. However, comprehensive assessments that integrate these risks with future cost projections for renewable energy, green hydrogen, and its synthetic downstream products are lacking. Using the Middle East and North Africa (MENA) as an example, this study introduces a novel approach that allows to incorporate mainly qualitative country-specific investment risks into quantitative analyses such as cost-potential and energy modelling. Our methodology calculates weighted average costs of capital (WACC) for 17 MENA countries under different risk scenarios, providing a more nuanced assessment compared to traditional models that use uniform cost of capital assumptions. The results indicate significant variations in WACC, such as between 4.67% in the United Arab Emirates and 24.84% in Yemen or Syria in the business-as-usual scenario. The incorporation of country-specific capital cost scenarios in quantitative analysis is demonstrated by modelling the cost-potential of Fischer-Tropsch (FT) fuels. The results show that country-specific investment risks significantly impact costs. For instance, by 2050, the starting LCOFs in high-risk scenarios can be up to 180% higher than in lower-risk contexts. This underlines that while renewable energy potential and its cost are important, it are the country-specific risk factors—captured through WACC—that have a greater influence in determining the competitiveness of exports and, consequently, the overall development of the renewable energy, green hydrogen and synthetic fuel sectors.